Synthesis of vegetable alkyl esters by using alkaline catalyst in the presence of alcohol derivatives as excess reactant - Azhari; Yunus, Robiah (Universiti Putra Malaysia, 2010)
Synthesis of vegetable alkyl esters was successfully carried out from vegetable triglycerides as feedstock by transesterification reaction under atmospheric pressure. In term of catalyst, alkaline was selected for this reaction. The effects of operating variables such as molar ratios, reaction temperatures were investigated as we". The reaction temperature and time were varied between 55 to 70°C and 50 to 90 minutes respectively. The alcohol derivatives to oil molar ratios were also varied at 6:1, 5:1, 4:1, and 3:1 to examine its effect on reaction yield. The reaction conversion was 99% by use of methoxide as a catalyst. However, with hydroxide as catalyst, the conversion was lower. The optimum conditions for methoxide as catalyst were reaction temperature, 65°C; reaction time, 60 minutes; molar ratio, 6:1; and catalyst amount, 1.0% w/w. The kinetics study on transesterification of vegetable triglycerides with alcohol derivatives established that the reaction occurred via two stepwise and irreversible elementary reactions under second order. A vacuum distillation process was used to reduce the alkyl esters saturated compounds that effect proportionally to pour point of vegetable alkyl esters. The lowest pour point attainable for vegetable alkyl esters was at -18°e.